Principles of ensuring as an innovative project - Tkachev, M. M.; Savchenko, O. I.; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2023)
The study of the principles of quality management of innovative projects shows that the key ones are: the principle of embedding in the project in advance of the requirements for the quality of innovative products; the principle of establishing quality in the scheme of innovations the project itself; the principle of self-control of quality; the principle of relying on statistical methods of control; the principle of attracting counterparties to the implementation of innovative projects to improve the quality of implementation.
Принципи забезпечення інноваційного проекту
Keywords: quality; system; innovative processes; business; efficiency